Proposed Business Strategy for Sibos Barbershop - kurnia, Indra; Motik, Suryani Sidik (The Indonesian Journal of Business Administration, 2015)
Abstract - This research is conducted to identify the positioning and design a business strategy for Sibos Barbershop, a barbershop company that has its branch in Condet, Jakarta, in order to be a competitive player in the growing industry. To achieve that goal, Sibos Barbershop has to identify its own strength and weakness, scan the industry environment, amplify its uniqueness, and formulate strategies that rely on the opportunities and threats to have a sustainable competitive advantage. The method used in this research are quantitative and qualitative, which quantitative method is using questionnaire and used as a tool to collect primary data. Qualitative method is using direct visit and open questionnaire to fit out the primary data. The result of both methods are used as factors in TOWS Matrix, Porter’s Generic, and Diamond Strategy. The result of the research are for Sibos Barbershop to accentuate its feature and develop the uniqueness deeper, avoid price competition if any, expand branches in terms of quality and quantity, maximize marketing especially in digital world, and to create some new revenue streams. Keyword: Business Strategy, Porter’s Generic, TOWS Matrix, Diamond Strategy, Barbershop